Mechanisms of lymphoid depletion in bowel obstruction - Lin, You-Min; Hegde, Shrilakshmi; Cong, Yingzi; Shi, Xuan-Zheng (Frontiers in Physiology, 2022)
Background and aims: Bowel obstruction (BO) causes not only gastrointestinal dysfunctions but also systemic responses such as sepsis, infections, and immune impairments. The mechanisms involved are not well understood. In this study, we tested the hypothesis that BO leads to lymphoid depletion in primary and peripheral lymphoid organs, which may contribute to systemic responses. We also sought to uncover mechanisms of lymphoid depletion in BO. Methods: Partial colon obstruction was induced with a band in the distal colon of Sprague-Dawley rats, and wild-type and osteopontin knockout (OPN−/−) mice. Obstruction was maintained for 7 days in rats and 4 days in mice. Thymus, bone marrow, spleen, and mesenteric lymph node (MLN) were taken for flow cytometry analysis. Results: The weight of thymus, spleen, and MLN was significantly decreased in BO rats, compared to sham. B and T lymphopoiesis in the bone marrow and thymus was suppressed, and numbers of lymphocytes, CD4+, and CD8+ T cells in the spleen and MLN were all decreased in BO. Depletion of gut microbiota blocked BO-associated lymphopenia in the MLN. Corticosterone antagonism partially attenuated BO-associated reduction of lymphocytes in the thymus and bone marrow. Plasma OPN levels and OPN expression in the distended colon were increased in BO. Deletion of the OPN gene did not affect splenic lymphopenia, but attenuated suppression of lymphopoiesis in the bone marrow and thymus in BO. Conclusions: BO suppresses lymphocyte generation and maintenance in lymphoid organs. Mechanical distention-induced OPN, corticosterone, and gut microbiota are involved in the immune phenotype in BO.